PENERAPAN METODE ARIMA BOX-JENKINS UNTUK MEMPREDIKSI HARGA SAHAM DI PT ANEKA TAMBANG TBK - Ilham Yusuf Triputra; Sufri Sufri; Sherli Yurinanda (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
A capital market is a market in which long-term trading of financial assets takes place, or a market in which various financial instruments are traded. The development of capital markets promotes the economic development of the country. The form of investment in the capital market is in the form of shares. Because stock prices are constantly fluctuating, capital market participants need analysis to help predict future stock prices. PT Aneka Tambang TBK or ANTM for short is one of the stocks traded in Indonesia's capital market. This study applied the Box-Jenkins ARIMA method for the period from July 2021 to November 2021 to determine the optimal forecast model for stock price fluctuations of ANTM, and obtained forecast results in December 2021. It is intended to The best preserved model is his ARIMA model (3,2,0) and ANTM's December 2021 stock price forecast results are down.